Pandemic vulnerability, policy feedback and support for immigration: Evidence from Asia. (4th March 2022) - Lee, Siu‐yau; Yuen, Samson; Or, Nick H. K.; Cheng, Edmund W.; Yue, Ricci P. H.
Abstract: Past studies have shown that disease threat increases people's hostility towards immigrants. However, in our survey ( N = 9571) conducted in five advanced Asian economies during the outbreak of COVID‐19, we found that COVID‐19 vulnerability was positively associated with support for immigration. Drawing on insight from policy feedback theories, we propose that the positive association is caused by the presence of widespread border crossing restrictions, which have changed the meaning and cost implications of COVID‐19. As the outbreak expands, the pandemic has become not just a threat to people's health but also a barrier to globalization. Consequently, people who are worried about the disease may see globalization processes, including migration, as signs of pandemic relief. We find supportive evidence in our analysis. First, the positive association between COVID‐19 vulnerability and support for immigration is more salient among respondents who considered restrictions on international travel to be stringent. Second, the positive association between COVID‐19 vulnerability and immigration attitude was mediated by perceived economic threat from the pandemic and contribution by immigrants towards the containment of the pandemic. These findings suggest that disease control measures adopted at the global level may alter certain widely accepted effects of disease threat on immigration attitudes.